2015
DOI: 10.1128/aem.00088-15
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Formation and Quorum-Sensing-Molecule Production by Clinical Isolates of Serratia liquefaciens

Abstract: AHLs. No correlation between biofilm formation and the production of large amounts of AHLs could be established. Fimbrialike structures were observed by transmission electron microscopy, and the presence of the type 1 fimbrial adhesin gene fimH in all strains was confirmed by PCR. The ability of S. liquefaciens to adhere to abiotic surfaces and to form biofilms likely contributes to its persistence in the hospital environment, increasing the probability of causing nosocomial infections. Therefore, a better und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 43 publications
3
26
0
Order By: Relevance
“…A wide range of intraspecific variability was also found in the AHL profile within A. baumannii clinical isolates, since OHC12-HSL was present in only 4 of 7 strains when cultured in the rich LB medium. Intraspecific variation in AHL profile has been also reported in other important pathogens, such as Serratia liquefaciens (Remuzgo-Martínez et al, 2015 ). In the case of A. baumannii , these differences could be derived from differences in the control of the expression of the abaI synthase that is present in all isolates, or in the QQ activity, that was also present in all of them.…”
Section: Discussionmentioning
confidence: 76%
“…A wide range of intraspecific variability was also found in the AHL profile within A. baumannii clinical isolates, since OHC12-HSL was present in only 4 of 7 strains when cultured in the rich LB medium. Intraspecific variation in AHL profile has been also reported in other important pathogens, such as Serratia liquefaciens (Remuzgo-Martínez et al, 2015 ). In the case of A. baumannii , these differences could be derived from differences in the control of the expression of the abaI synthase that is present in all isolates, or in the QQ activity, that was also present in all of them.…”
Section: Discussionmentioning
confidence: 76%
“…AHLs were identified and confirmed by comparing the retention times and the spectra with synthetic standards (C6‐HSL, C10‐HSL, 3OC10‐HSL, and C12‐HSL; Sigma). The AHL content was measured by comparison with a calibration curve generated with each of the appropriate AHL synthetic standards (Remuzgo‐Martínez et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…Nonetheless, Remuzgo‐Martínez et al. () showed that clinical isolates of S. marcescens formed denser biofilms at 24 °C than at 37 °C on plastic surfaces. These evidences suggest that incubation temperature is a determining factor in bacterial BF, since microorganisms might adapt differently in the environment or in the host depending on the temperature, among other factors.…”
Section: Resultsmentioning
confidence: 99%